Bases for trust in pension funds operating in Poland - Marzec, Małgorzata (Research Papers of Wrocław University of Economics, 2018)
The purpose of this article is to analyze the trust in Open Pension Funds (OPF) as entities operating in the Polish pension system. The task of OPFs is to collect and manage the funds accumulated by Poles in order to secure their capital after retirement. Poles often ignore the need to save money for old age, despite the fact that the Polish pension system provides for individual pension schemes. This article indicates the factors for building the trust in OPFs as institutions operating within the second pillar of the pension system. The trust in the pension system can be built through the trust in the individual institutions operating in the given system. Separating trust factors related to OPFs can indicate the methods of building the trust in the entire pension system
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 111-124
Keywords: trust; pension system; pension funds; zaufanie; system emerytalny; fundusze emerytalne